A VENDIAN (590±5 MA) AGE FOR THE PADORA GROUP IN THE BAIKAL-MUYA FOLDBELT: EVIDENCE FROM U-PB ZIRCON DATA - Rytsk E.Yu.; Makeev A.F.; Glebovitsky V.A.; Fedoseenko A.M. (My University, 2004)
The metamorphosed and severely deformed Upper Riphean rocks of the Baikal-Muya Foldbelt (BMFB) including ophiolite fragments of disputable origin are overlain with angular unconformity (locally, basal conglomerate) by a terrigenous-carbonate sequence of superimposed basins. According to the traditional interpretation [4, 5], the carbonate units crowning the section are reliably characterized by Early Cambrian fauna while the underlying barren terrigenous rocks are Vendian (<650 Ma) in age. However, the results of recent geochronological studies indicate that the deep metamorphic and mantle igneous rocks of the BMFB were formed 0.60-0.65 Ga ago in the early Vendian. In order to solve this contradiction and determine the upper age limit of the folding and metamorphism in the BMFB, we studied the acid volcanics of the Padora Group).
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский